Liquidity: essence, risk, institutions, markets and regulation: a report of the liquidity working party. (12th February 2016) - Keating, C.; Hatchett, J.; Smith, A.; Walton, J.; Zhao, T.
Abstract: This study is a subjective synthesis of the work of many academics, supervisors and practitioners on the topic of liquidity and many of its multiple aspects. It borrows heavily and freely from those works in the pursuit of coherence, as this subject can be both confused and confusing. Although many hypotheses, both established and speculative, are referred to, none is proposed in this paper. In order to be of possible use to a range of readers, it roams from the most basic and elementary to some of the most recent and advanced. In pursuit of brevity and readability, in many instances it can do little more than introduce a particular feature and leave further investigation to the reader. Liquidity is clearly a topic with much unfinished business. Our ambition in writing this paper is threefold: first, to raise awareness amongst actuaries of the wide-ranging implications for actuarial work of liquidity; second, to bring some coherence to the manifold measures and uses of the concept of liquidity by attempting to synthesise some of the key elements of knowledge today; finally, to highlight some of the more high profile and open questions relevant for actuarial work. This paper makes many references to behaviour during the crisis and its aftermath; however, it is not intended to be a forensic analysis of the crisis attributing causality. The crisis has simply served as an experiment during which many things became observable.